Controlling the conductivity of Ti3C2 MXenes by inductively coupled oxygen and hydrogen plasma treatment and humidity. Issue 22 (24th February 2017) - Römer, Florian M.; Wiedwald, Ulf; Strusch, Tanja; Halim, Joseph; Mayerberger, Elisa; Barsoum, Michel W.; Farle, Michael
Abstract : With oxygen and hydrogen plasma the resistivity of transparent MXene electrodes can be controlled. Abstract : We report on the effects of plasma treatment and humidity on the electrical conductivities of Ti3 C2 MXene thin films. The latter – spincoated from a colloidal solution produced by LiF/HCl etching of Ti3 AlC2 powders – were 13 nm thick with an area of 6.8 mm 2 . The changes in the films exposed to hydrogen (H) and oxygen (O) plasmas in vacuum were analyzed by X-ray photoelectron spectroscopy. We find that the film resistivities can be switched reproducibly by plasma treatment between 5.6 μΩm (oxidized state) to 4.6 μΩm (reduced state). Both states show metallic like conductivity. In high vacuum, the film resistivity was 243 Ω; when the relative humidity was 80% the film resistance increased to 6340 Ω, a 26 fold increase.